2014
DOI: 10.1371/journal.pone.0110385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vivo Morpholino Knockdown of Lateral Hypothalamus Orexin/Hypocretin on Renewal of Alcohol Seeking

Abstract: Two experiments used vivo morpholinos to assess the role of orexin/hypocretin in ABA renewal of extinguished alcohol seeking. Rats were trained to respond for alcoholic beer in a distinctive context, A, and then extinguished in a second distinctive context, B. When rats were tested in the extinction context, ABB, responding was low but when they were tested in the training context, ABA, responding was significantly higher. Microinjection of an orexin/hypocretin antisense vivo morpholino into LH significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Evidence supporting a role for endogenous MCH in stimulating alcohol intake comes from a study showing peripheral administration of an MCHR1 antagonist to suppress alcohol self-administration and cue-induced reinstatement of alcohol-seeking (Cippitelli et al, 2010). Moreover, a recent study using antisense vivo morpholinos that reduce MCH and OX protein levels reported that this reduced the renewal of extinguished alcohol seeking (Prasad and McNally, 2014), lending further support to the idea that MCH does endogenously promote alcohol intake.…”
Section: Neuropeptides With Complex Relationships To Alcoholmentioning
confidence: 76%
See 1 more Smart Citation
“…Evidence supporting a role for endogenous MCH in stimulating alcohol intake comes from a study showing peripheral administration of an MCHR1 antagonist to suppress alcohol self-administration and cue-induced reinstatement of alcohol-seeking (Cippitelli et al, 2010). Moreover, a recent study using antisense vivo morpholinos that reduce MCH and OX protein levels reported that this reduced the renewal of extinguished alcohol seeking (Prasad and McNally, 2014), lending further support to the idea that MCH does endogenously promote alcohol intake.…”
Section: Neuropeptides With Complex Relationships To Alcoholmentioning
confidence: 76%
“…While OX on its own is not necessary for renewal of alcohol seeking, it may work in concert with other neuropeptides to induce this behavior (Prasad and McNally, 2014). Specifically, an OX antisense vivo morpholino microinjected into the LH diminished renewal of alcohol seeking when injected at a level that reduced both OX and MCH protein but not at a level that reduced only OX protein (Prasad and McNally, 2014). While hypothalamic OX is therefore capable of promoting alcohol drinking, it may not be sufficient for the execution of this behavior.…”
Section: Neuropeptides With a Positive Feedback Relationship To Almentioning
confidence: 99%
“…The impacts of direct manipulation of the orexin system generally agree with these findings. Consistent with the robust recruitment of lateral orexin neurons during context‐induced reinstatement of cocaine seeking, this reinstatement is prevented by pretreatment with SB‐334867 (0–30 mg/kg) (Smith et al ), whereas selective knockdown of orexin protein expression does not prevent context‐induced reinstatement of alcohol seeking (Prasad & McNally ).…”
Section: Hypothalamusmentioning
confidence: 77%
“…Another prominent subpopulation of LH neurons expresses MCH, which are distinct from OX neurons. Prasad et al [67] examined the involvement of OX and MCH on ABA renewal of alcohol seeking. [67].…”
Section: Ox Loci-specific Targetingmentioning
confidence: 99%
“…Prasad et al [67] examined the involvement of OX and MCH on ABA renewal of alcohol seeking. [67]. Long-Evans rats were injected with an antisense morpholino (0.6 nM), which knocked down 50 % of OX protein expression in the LH, without affecting MCH protein expression.…”
Section: Ox Loci-specific Targetingmentioning
confidence: 99%